2016
DOI: 10.1590/1678-457x.0092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oil-water mixed frying and pure-oil frying on the quality characteristics of soybean oil and chicken chop

Abstract: The effects of oil-water mixed frying (DWF) and pure-oil frying (PDF) on changes in quality characteristics of soybean oil and chicken chop during six days of frying were comparatively investigated. The results showed that the changes in specific extinction coefficients, p-anisidine value, carbonyl value, viscosity and color of soybean oil were more pronounced in the case of PDF, indicating that oil oxidative and polymeric degradation was retarded by DWF. Concerning fat content of chicken chop, lower (p<0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 41 publications
3
29
0
5
Order By: Relevance
“…K 232 is highly associated with the amount of conjugated dienes as a consequence of primary oxidation of polyunsaturated fatty acids. However, K 268 is more correlated to the presence of secondary oxidation compounds such as conjugated trienes and carbonyl compounds [54]. Changes in K 232 and K 268 values are shown in Table 5.…”
Section: Specific Extinction Coefficients Measurementmentioning
confidence: 99%
“…K 232 is highly associated with the amount of conjugated dienes as a consequence of primary oxidation of polyunsaturated fatty acids. However, K 268 is more correlated to the presence of secondary oxidation compounds such as conjugated trienes and carbonyl compounds [54]. Changes in K 232 and K 268 values are shown in Table 5.…”
Section: Specific Extinction Coefficients Measurementmentioning
confidence: 99%
“…It is suggested that measures should be taken to slow down the hydrolysis rate of oil in the process of oil-water mixed frying in the future. [35] Spray frying Low fat content Better color of products (lighter)…”
Section: Vacuum Frying (Vf)mentioning
confidence: 99%
“…In this approach, the food residue falls into water, which prevents it from depositing in the oil and being fried repeatedly. The water-oil mixing technology reduces the occurrence of coking and carbonization of residues in oil, which slow-downs the increase in turbidity of frying oils and reduces the deterioration of their quality [113].…”
Section: Water-oil Mixed Fryingmentioning
confidence: 99%
See 1 more Smart Citation
“…The deep-frying process of pempek with a high temperature of around 165-190 °C can cause mass food transfer, oil and air simultaneously encourage physical and chemical changes so that water loss, oil absorption, color change, flavor development, gelatinization, and oil oxidation will occur (Ma et al, 2016). The oil content in pempek is easily oxidized when exposed to oxygen which can cause rancidity (Ketaren, 2008).…”
Section: Introductionmentioning
confidence: 99%